Determination and numerical simulation for HJC constitutive model parameters of Jinping marble. Issue 3 (October 2021) - Lou, C D; Zhang, R; Ren, L; Zhou, J F; Peng, Y; Zhang, Z T
Abstract: Holmquist-Johnson-Cook (HJC) constitutive model has been widely used in dynamic response analysis of concrete-like materials under impact and explosion. Based on the available data from uniaxial compression tests, triaxial compression tests, Brazilian splitting tests as well as SHPB experiments of 2400 m deep Jinping marble, a set of HJC model parameters suitable for high strength brittle marble were determined. Then, on the basis of one-dimensional static dynamic combined SHPB experiments, the numerical simulation of one-dimensional static dynamic combined SHPB experiments of Jinping marble were carried out by LS-DYNA software. Comparing the experimental and numerical simulation results, the rationality of the model parameters was verified. The numerical simulation results show that: from the perspective of stress-strain curve, the numerical simulation curve is consistent with the experimental curve, and the deviation of peak strength is less than 5%; from the perspective of damage evolution, the marble in the one-dimensional static and dynamic combined SHPB experiments are mainly tensile splitting failure. With the increase of prestress, the more serious the crack expansion and internal damage, the more broken the rock interior. Finally, the sensitivity of each parameter in the model is quantitatively calculated, and the high-sensitivity parameters are G, B, f c, S max, μ c and K 1, which should be accurately obtained based on experiments.